3D surface characterization of polymer-oxide nanocomposite coating using nanoscale stereometric approach for enhanced functionality - Ţălu, Ştefan; Patra, Niranjan (Colloids and surfaces. A, Physicochemical and engineering aspects, 2025)
This study investigates the influence of varying nanorods (NR) filler concentrations (0, 5, 10, 20, and 30 wt%) on the surface morphology of nanocomposite coating composed of a poly(methyl methacrylate) matrix containing elongated titania nanorods, applied via spin-coating. Detailed analyses of 3-D topographic AFM images, contour line plots, Abbott-Firestone curves, furrow depth, texture direction, power spectral density (PSD), and ISO 25178–2:2012 statistical surface parameters were conducted. Results revealed a significant increase in surface roughness and complexity with increasing NR content, peaking at 20 wt% (P20). P20 demonstrated the highest roughness, optimal texture alignment, and functional properties, while further increases in NR content (P30) led to surface smoothing due to filler agglomeration. These findings highlight the critical role of NR concentration in tailoring the surface properties of nanocomposite films for enhanced performance. [Display omitted] •Optimized 20 wt% nanorods yield peak surface roughness and functionality.•High nanorod concentrations smooth surfaces and reduce coating performance•AFM and stereometric analysis reveals nanoscale surface evolution with nanorod content.•Enhanced roughness improves adhesion and functional surface properties.•Fractal analysis highlights surface complexity with varying nanorod concentrations.